Systematic Literature Review of SEP-Based Clustering Protocols in Wireless Sensor Networks: Taxonomy, Critical Analysis, and Adaptive Multi-Parameter Framework Proposal - Dian Neipa Purnamasari; Muhhammad Iyan Putra Pratama (Journal of Renewable Energy and Smart Device, 2026)
Clustering protocols derived from the Stable Election Protocol (SEP) have been extensively studied for improving energy efficiency in heterogeneous Wireless Sensor Networks (WSNs). However, existing studies remain fragmented, with inconsistent evaluation settings, non-standardized performance metrics, and limited analysis of parameter sensitivity, making cross-study comparison unreliable. This paper presents a PRISMA-guided Systematic Literature Review (SLR) of 42 primary studies published between 2021 and 2026. The review classifies SEP-based approaches into four categories: energy-based (33%), distance-aware (24%), AI-based (21%), and hybrid (21%), and critically evaluates their methodological rigor. The analysis reveals three key research gaps: lack of evaluation standardization, insufficient exploration of heterogeneity parameters, and absence of realistic deployment scenarios. To address these issues, this study proposes ADSEP (Adaptive Dynamic SEP), a three-layer conceptual framework integrating energy normalization, spatial awareness, and adaptive routing strategies. Unlike prior work, ADSEP is positioned as a structured research direction with a defined validation protocol rather than a standalone protocol. This work contributes not only a taxonomy and critical synthesis of SEP-based protocols but also establishes a principled roadmap for future research in heterogeneous WSN clustering.